PENGARUH TINGKAT PENDIDIKAN FORMAL DAN PEMAHAMAN AGAMA ISLAM ORANG TUA TERHADAP KECERDASAN SPIRITUAL ANAK DI DESA TANJUNG AGUNG KECAMATAN SEGINIM - Deko Rio Putra (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
This research aims to: (1)  the  effect of formal  education levels of parents of spiritual  intelligence of children in the  village of Tanjung Agung, (2)  the  effect of the  understanding of Islam parent to spiritual  intelligence of children in the  village of Tanjung Agung, (3)  the  effect of educational level formal  and  understanding of the  Islamic religion to the  intelligence of the  spiritual  parents of children in the  village of Tanjung Agung. Research  variables are considered: (1)  the  independent variable (X11)  is the  formal  education level of parents, (2)  the  independent variable (X12)  which is understanding Islam parents, (3)  the  dependent variable (Y) that  is spiritual  intelligence of children in the  village of Tanjung Agung. The  results  of the  analysis of these  data  is a positive relationship between  the  effect of formal  education levels  of  parents of  spiritual   intelligence  of  children in  the  village  of  Tanjung Agung,  according  to  the  statistical hypothesis  proposed Ho:   y1 < 0, Ha:   y1> 0, because  the  price  of     greater than  0 ( 0,146> 0),  it can  be  concluded there is a positive and  significant  relationship between  the  effect of 0,146 formal  education levels of parents of spiritual intelligence of children in the  village of Tanjung Agung.  As for the  influence of the  understanding of Islam parent to spiritual  intelligence of children in the  village of Tanjung Agung  is a positive  relationship, according to the  statistical hypothesis  proposed Ho:   y2 < 0, Ha:   y2 > 0, because  the  price  of    greater than  0 (0.717  > 0) , it can  be concluded there is a positive and  significant  correlation of 0.717 between  the  influence of Islamic religious  understanding of parents of spiritual  intelligence of children in  the  village of Tanjung Agung.  The  results  of the  regression analysis contained significant  influence between  the  level of formal  education and  understanding of the  Islamic  religion to the  spiritual intelligence of parents of children in the  village of Tanjung Agung based  on  the  calculated value F is greater than  the value of table  F, that  of F = 16.95 and  Ftabel  = 3, 35, so that  the  calculated value F is the  rejection region of Ho.  To contribute jointly  (simultaneously) variables  X1 and  X2 to  Y  is 0.524 or  (RX1Y, X2Y = 0.524).  Because  the  value of r count>  0 or  0.524> 0, so Ha  is received.  It can  be  concluded there is a positive  and  significant  correlation of 0.524. Thus  the  researchers suggested  that  the  Spiritual  Intelligence was associated  with the  level of formal  education and understanding of Islam parents. for the  good  and  the  least spiritual  intelligence of the  child  depends on  the  level of formal  education and  understanding of Islam parents